Tuba-ovarian auto-amputation caused by ovarian teratoma in an adolescent girl - Atıcı, Ahmet; Yılmaz, Engin; Karaman, Ayşe; Apaydın, Sema; Afşarlar, Çağatay Evrim (The Turkish Journal of Pediatrics, 2017)
Ovarian auto-amputation is an extremely rare condition commonly encountered in the perinatal period. Spontaneous or secondary torsion of the ovary caused by an ovarian lesion may result in infarction and subsequent auto-amputation of the ovary. This paper demonstrates a case that underwent laparoscopic appendectomy with an incidental calcified auto-amputated right ovary. A 16-year-old adolescent girl was admitted to our department with a history of one-day abdominal pain. Physical examination of the patient revealed abdominal tenderness and rigidity on right lower quadrant. Her white blood cell count was 11x103/mL, and C-reactive protein was 69 mg/L. The patient underwent a laparoscopic appendectomy with a provisional diagnosis of acute appendicitis, and further exploration revealed a 2x2 cm white ovoid mass floating freely in the pelvis. The left ovary was clearly identified in its usual localization, but the right tuba was blindly ending without any fimbria or ovary. Postoperative course of the patient was uneventful, and she was discharged on postoperative day 2. The histopathological examination revealed a necrotic calcified ovarian teratoma. Auto-amputated ovary is a rare occasion mostly encountered during perinatal period, and it may be unilateral or bilateral. An auto-amputated ovarian mass may rarely be a teratoma although the most common cause of auto-amputation during perinatal and adolescent period is ovarian torsion due to an ovarian cyst.
Keywords: adolescent; auto-amputation; ovary; teratoma